The Bali Agreement: An assessment from the perspective of developing countries - Díaz-Bonilla, Eugenio; Laborde Debucquet, David (International Food Policy Research Institute, 2015)
This paper discusses the different agreements and decisions reached in the Bali Ministerial Conference and the potential implications for the post-Bali work program. The results of the Bali Ministerial Conference are analyzed taking the perspective of the developing countries (though recognizing that this is a heterogeneous group). Because agricultural topics—in particular, food security—have been key issues in the negotiations, they receive a more detailed treatment. It is recognized, however, that discussing agricultural issues in isolation will not provide an adequate picture of the Bali negotiations. Therefore, this paper provides some historical and conceptual background on each of the topics negotiated, while also including enough legal detail regarding the texts and specific trade discussions to serve as a basic reference. Besides the specific substance of the agreements and decisions, a general important consideration is that, given the fears that a failure in Bali would have led to further fragmentation of the global trading system and the marginalization of many developing countries due to increasing imbalances in negotiating power, the Bali agreements and the November 2014 decision reinforce the WTO as the multilateral anchor of the global trade system. Notwithstanding potential criticisms about the limitations of the Bali agreements, developing countries should consider the strengthening of the multilateral system as a positive development: to the extent that individually many of them remain small players in the global arena, they should have a strong interest in a transparent, rule-based multilateral trading system that limits old-style power politics in global trade.